The Role of Augmented Reality (AR) in Interactive Learning for Children - Emeka Kelechi; Chidi Obi Nnaji (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Augmented Reality (AR) offers innovative ways to enhance interactive learning experiences for children by overlaying digital content onto the real world. This paper explores the effectiveness of AR applications in education, focusing on how AR can foster engagement, creativity, and critical thinking. The study examines AR-based educational tools and games designed to enhance learning across subjects like history, mathematics, and science.